SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU DI LINGKUNGAN SEKOLAH - Endang Palupi; Imas Sukmaswati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study originated from an unfavorable increase in students. This research is a descriptive research which is a research method designed to describe the events that exist and are still ongoing until now or at the present time. Suggestions used in this study are qualitative to discuss social phenomena from the perspective of participants. Thus, this qualitative research is research that is used to examine natural tourism objects where researchers are key instruments that collect qualitative data, namely 1). interview, 2). observation, 3). documentation, and 4). focused discussion (Focus Group Discussion). With the existence of this study, the poor teacher research after supervision by the school principal has increased and it is better to positively improve students and teaching and learning activities in schools can go according to the intended goals.